PELAKSANAAN MODEL PROBING-PROMPTING PADA PELAJARAN SOSIOLOGI SISWA XI IPS 1 SMA NEGERI 3 PONTIANAK - Rasina, Rasina; Okianna, Okianna; Hidayah, Riama Al (Universitas Tanjungpura, 2023)
This research is entitled